Prototipe dengan Sistem IoT Pada Pengaturan Suhu dan Kelembaban Pada Permentasi Tempe - Mekongga, Ikhthison; Mustaziri; Fazarrudin, Muhammad; Asrafi, Ibnu; Aryanti, Aryanti (Jurnal Ampere, 2023)
This research aims to design an IoT-based prototype for temperature and humidity control to enhance the productivity of tempe fermentation. The prototype utilizes the WeMos D1 R2 microcontroller, processing data from the temperature sensor (DHT11) and RTC DS3231 to control a DC fan and heater. The Blynk application enables remote monitoring and management of temperature and humidity. Research results indicate stable temperature (30°C–37°C) and humidity (60–70 RH). The prototype demonstrates effectiveness in controlling tempe fermentation conditions and is suitable for implementation. .